Modeling Business Processes for Heat Pump Sales and Configuration: A Low-Code Platform Approach - Tadeusz NOWICKI; Małgorzata OLEŚ-FILIKS; Agnieszka WARCHULSKA (Communications of International Proceedings, 2025)
This study addresses the challenge of selling and configuring heat pumps, a complex process requiring specialized expertise. A notable gap exists in the literature regarding the specific use of low-code platforms to model and implement business processes for heat pump sales and configuration. The methodology involved modeling sales and installation workflows using Business Process Model and Notation (BPMN), followed by the development and evaluation of a prototype on the Aurea low-code platform. The research resulted in the successful design and large-scale implementation of this web-based system in the Polish market. The findings confirm that the low-code platform significantly streamlines operations, reduces offer preparation time, and improves sales efficiency. This implementation serves as a viable proof of concept and a foundational reference for creating scalable business solutions in the renewable energy sector.
Keywords: low-code platform; heat pumps; renewable energy sources; system design; business process modeling